Very Mild Dementia and Medical Comorbidity Independently Predict Health Care Use in the Elderly - Ellen Grober PhD; Amy Sanders MD; Charles B. Hall PhD; Amy R. Ehrlich MD; Richard B. Lipton MD (SAGE Publishing, 2012)
Objective : To determine whether dementia status and medical burden were independent predictors of emergency department (ED) visits and hospitalizations in older patients from an urban geriatric practice participating in a primary care based cognitive screening program. Participants and Methods : A comprehensive chart review was conducted for 300 African American and Caucasian patients, including 46 with prevalent dementia and 28 with incident dementia using the Cumulative Illness Burden Scale. Hospital-based claims data was used to retrieve ED visits and hospital admissions for 5 years following baseline assessment. Results : Patients with dementia had a 49% higher rate of ED visits (IRR = 1.49; 95% CI = 1.06, 2.09) and an 83% higher risk of death than patients without dementia (HR = 1.83; 95% CI = 3.07, 0.03). Dementia status predicted hospital admissions after adjustment for medical burden (IRR = 1.37; 95% CI = 0.99, 1.89). For each one point increase in medical burden, there was an 11% increase in ED visits (IRR = 1.11; 95% CI = 1.06, 1.16), a 13% increase in hospital admissions (IRR = 1.13; 95% CI = 1.09, 1.17), and an 11% higher risk of death (HR = 1.11; 95% CI = 1.04, 1.17). Age did not predict utilization. Conclusion : Dementia status and medical burden were independent predictors of ED visits and death in patients with clinically diagnosed dementia followed from the early stage of disease.